Implementation of the Psychological Scale Depression Anxiety Stress Scale 21 (Dass-21) in the Expert System for Diagnosing Mental Health Disorder - Mola, Sebastianus Adi Santoso; Melly, Margaretha Delima; Yublina Pandie, Emerensye Sofia (Institut Teknologi Dirgantara Adisutjipto, 2024)
Mental health is something that needs to be considered properly because if the mental is disturbed then the body also feels the impact. Mental health disorders including depression, stress, and anxiety can affect anyone, especially students. Due to the lack of awareness of mental health in students and the minimal number of clinical psychologists in Indonesia, students are reluctant to see a psychologist. The existence of an expert system for early detection of mental health disorders using the Depression Anxiety Stress Scale (DASS-21) with 21 symptoms can help students analyse the level of mental health disorders which are divided into depression, stress, and anxiety. The results of the study based on 100 student data of Nusa Cendana University obtained the system can diagnose mental health disorders including depression, stress, and anxiety with an accuracy rate of expert and system results of 100% which shows that the implementation of the DASS-21 instrument into the system is correct. Findings from the diagnosis results show that most students (70%) suffer from anxiety in the moderate to severe category. However, special attention needs to be paid to students who suffer from moderate to severe depression (37%) and severe to moderate stress (36%).